7 PENYEBAB BANJIR DI WILAYAH PERKOTAAN YANG PADAT PENDUDUKNYA - Rahardjo, Petrus Nugro (Jurnal Air Indonesia, 2014)
In Indonesia during the rainy season floods often occur in urban areas, especially in a very densely populated areas. Central or local government has always suffered huge losses due to widespread flooding and paralyze all activities of the city. So many environmental issues that can cause flooding and the problem has become very complex. By doing assessment study deeply it can be seen that there are 7 (seven) causes flooding, namely: there is not environmentally sustainable development; The lack of a clean lifestyle in the general public; The lack of planning and maintenance of good drainage; The lack of consistency from the authorities in Spatial Planning and Regional; The absence of good conservation programs in balancing environmental of water; Iand subsidence; and very high rainfall intensity. Therefore it is necessary for serious efforts to address the flooding problem through: The consistency in environmentally sustainable development; Clean lifestyle in the community; The application of the concept " Water front City "; The application of the concept " One River One Management "; Making Infiltration; Prevention of Land Subsidence by Groundwater Injection manner; and Improved coordination of all stakeholders.Ã‚Â Keywords: Causes flooding, options in handling flood problem.